2015
DOI: 10.1523/eneuro.0006-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

LRP1 Downregulates the Alzheimer’s β-Secretase BACE1 by Modulating Its Intraneuronal Trafficking

Abstract: The β-secretase called BACE1 is a membrane-associated protease that initiates the generation of amyloid β-protein, a key event in Alzheimer’s disease. However, the mechanism of inraneuronal regulation of BACE1 is poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 64 publications
(98 reference statements)
4
16
0
Order By: Relevance
“…To gain further insights into the mechanism underlying Aβ-O-induced elevation of BACE1, we analyzed the influence of Aβ-O on intraneuronal localization of BACE1 using immunocytochemistry. In control untreated neurons, endogenous BACE1 immunoreactivity was observed in neuronal soma and neurites, consistent with recent findings [ 23 , 24 ]. Interestingly, in neurons treated with Aβ-O for 3 days, the intensity of BACE1 immunoreactivity was higher relative to control, although levels in soma were comparable between control and Aβ-O-treated neurons (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To gain further insights into the mechanism underlying Aβ-O-induced elevation of BACE1, we analyzed the influence of Aβ-O on intraneuronal localization of BACE1 using immunocytochemistry. In control untreated neurons, endogenous BACE1 immunoreactivity was observed in neuronal soma and neurites, consistent with recent findings [ 23 , 24 ]. Interestingly, in neurons treated with Aβ-O for 3 days, the intensity of BACE1 immunoreactivity was higher relative to control, although levels in soma were comparable between control and Aβ-O-treated neurons (Fig.…”
Section: Resultssupporting
confidence: 92%
“…5 ). A few molecules are involved in BACE1 degradation, among which GGA3 has been most extensively investigated [ 14 , 24 , 32 , 33 ]. GGA3 appears to participate in BACE1 sorting from endosomes to lysosomes, and caspase-mediated depletion of GGA3 stabilizes BACE1 [ 14 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…BACE1 structure, subcellular localization and/or activity are modulated by interaction with a large number of proteins including BRI3, GGA's, LRP1, and nicastrin among others. [41][42][43] We have shown that FIGURE 6 ORP150 regulates BACE1 expression under ER and oxidative stress. A, HEK293-BACE1 stable cells were treated with 4 and 10 μg/mL of tunicamycin for ER stress.…”
Section: Discussionmentioning
confidence: 97%
“…Jaeger et al (72) also revealed that dysfunction of LRP1 at the blood brain barrier may be associated with increased Aβ accumulation and progression of AD. Recently, LRP1 was associated with downregulation of β-site APP-cleaving enzyme 1 (BACE1) and, thus, affects generation of Aβ by cleavage of the APP (73).…”
Section: Angiotensin-converting Enzyme (Ace)mentioning
confidence: 99%